Wayang Kulit Kelantan: A Study of Characterization and Puppets - Yousof, G.S.; Khor, K.K. (University of Hawaii Press, 2017)
This paper examines the principal characters of the Malay versions (Hikayat Seri Rama and Hikayat Maharaja Wana) of the Hindu epic Ramayana, which provides the source material for the Malaysian shadow play, wayang kulit kelantan. The characters are organized into several categories according to whether they are gods, human beings, demons, apes, or lesser creatures. Following that, the paper makes an analysis of eleven characters selected from the categories mentioned, as well as puppets representing them, through the Indonesian-Malay halus-kasar (refined-coarse) theory of aesthetics. Although important and appropriate to proper appreciation of Indonesian and Malay arts forms, the theory has not previously been applied to wayang kulit kelantan.